Research trends around open innovation in higher education: advancements and future direction - Valencia-Arias, Alejandro; Gómez-Bayona, Ledy; Moreno-López, Gustavo; Sialer-Rivera, Noelia; Bernal, Olga-Vélez; Gallegos, Ada; Arias-Vargas, Francisco Javier (Frontiers in Education, 2023)
Open innovation in education fosters collaboration between internal and external actors, adapting to new forms of teaching and learning, and has a positive impact on the economy by overcoming barriers to technology transfer. The methodology used was a review based on the PRISMA statement and the main results allow us to identify that literary production has increased in recent years and that the main countries of academic progress are the United Kingdom and Spain. The research trends are i) Technology Transfer because of open innovation strategies involving universities and enterprises, ii) derivations of the promotion that innovation policies can exert on open innovation in terms of diversification of business models, iii) Factors that influence or determine the collaboration between companies, generally from the industrial sector, with universities, within the framework of open innovation and iv) Education 4. 0 in terms of the design and implementation of new educational systems involving new technologies and learning activities. Relevant topics such as knowledge transfer and management and entrepreneurship have been identified as fundamental for learning and supporting the education sector, particularly universities. These trending topics benefit students, graduates, and the wider community. It is recommended to conduct further in-depth research on these topics in the future.